CONSEQUENCES OF CHRONIC WOUNDS ON PATIENT’S LIFE - Ivanková, V.; Belovičová, M. (Україна. Здоров’я нації, 2023)
Modern medicine and nursing call for the need for comprehensive treatment and patient care and for an individual approach to the treatment of chronic wounds. It is necessary to perceive the patient as a holistic being and to comprehensively evaluate all factors influencing the wound healing process.